COMPETITIVENESS OF THE CORN AGRIBUSINEES CLUSTER - Haryono, Iranita; Hartina, Hartina; Rasul, Muhammad (Universitas Muhammadiyah Sidenreng Rappang, 2021)
ABSTRACT The existence of clusters provides great benefits in regional economic development, as revealed by the results of research [1] that the cluster approach can significantly improve the regional economy in a more effective and efficient manner and accelerate overall national economic development so as to increase existing competitiveness in the area. The corn agribusiness cluster in Gowa Regency occurs naturally (traditionally) which begins with the emergence of several corn cultivation businesses in certain districts, and over time this corn cultivation business is able to attract other parties to support their activities, especially players in the upstream and downstream sector actors. Then if an exchange takes place continuously for a long time, it will crystallize into a network of social relations and it is hoped that it can increase the competitiveness of corn. With this, the aim of this research is to analyze the competitiveness of the corn agribusiness cluster. This research was conducted in Gowa Regency. The choice of research location was carried out deliberately (purporsive sampling) with the consideration that the area is one of the centers of corn production in South Sulawesi Province. The research was conducted from November 2019 to December. The analysis was carried out using descriptive statistical analysis methods with a scoring rating. The competitiveness of corn in Tompobulu District, Gowa Regency is 805. This score can be interpreted into a strong category score. Key words: Competitiveness, cluster, corn